Historical review of the ancient method of treatment “Cup Therapy” and its legal status - Ahmed Ali; Shabana Qazi; Arif Mahmood Mustafai (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
In Islam, healing is Sunnah. An ancient form of healing is "Cupping Therapy (i.e. Hijama)" that has been around for centuries. What was the importance of Cupping Therapy (i.e. Hijama) in the sight of the Prophet (peace and blessings of Allah be upon him) and the sight of the Companions, how they considered Cupping Therapy (i.e. Hijama) as a necessary and useful treatment, can be gauged from the fact that there are 70 hadiths in the collection of hadiths on the subject of Cupping Therapy (i.e. Hijama) more than forty ahaadeeth are "Saheeh (i.e. Authentic)" in terms of authenticity and the remaining thirty ahaadeeth are "da'eef (i.e. unauthentic)".Cupping Therapy (i.e. Hijama) is a multi-purpose treatment along with the Sunnah of the Prophet (peace and blessings of Allah be upon him). The best days for Cupping Therapy (i.e. Hijama) are the 17th, 19th and 21st of the lunar date. Cupping Therapy (i.e. Hijama) features that distinguish it from other treatments and make it superior to other methods: (1) Cheap treatment (2) Immediate and short term treatment (3) Pain-free treatment: (1) Free from side effects and (2) The Sunnah is to be prophetic